Research on Two-stage Multi-objective Integer Programming Model of Helicopter Distribution Materials in Emergency Logistics - Guo, Haiwang; Peng, Chaojing (IOP conference series. Materials Science and Engineering, 2019)
Based on the earthquake disaster, this paper introduces the JIT just-in-time thinking of logistics management, and builds a three-level supply chain network consisting of helicopters, warehouses and material demanders. On this basis, aiming at maximizing the seismic performance, radiation range and optimal helicopter dispatching plan of the material reserve, and establishing the warehouse location and material distribution as the decision variables, a two-stage multi-objective integer programming model is established. The feasibility and effectiveness of the model are verified by specific case analysis, and the efficiency and effect of material distribution in the earthquake disaster reduction system are improved. In addition, according to the actual earthquake disaster area, the model was improved by the ant colony optimization algorithm.